Electrochemical oxidation of tamoxifen revisited - Garrido, Jorge (2014)
Tamoxifen is a selective estrogen receptor modulator that is used as an adjuvant and/or chemotherapeutic agent for the treatment of all stages of hormone-dependent breast cancer. Currently there is a deep interest in the study of tamoxifen biotransformation and identification of metabolites since they can significantly contribute to the overall pharmacological or adverse effects of the drug. Accordingly, the study of the electrochemical behavior of tamoxifen in aqueous solution is reported. To clarify the occurring oxidative process and to assess the influence of the functional groups on the oxidation mechanism, the voltammetric assessment was extended to the study of tamoxifen’s analogues (E)-tamoxifen and dihydrotamoxifen, and to its main phase I oxidative metabolite, N-desmethyl tamoxifen. The data found shows that the oxidative processes occurring in tamoxifen are essentially related with the two chemical moieties present in the molecule: the substituted aromatic nucleus and the tertiary amine group. Moreover, the results obtained suggest that the ethylenic linkage is not critical for tamoxifen’s oxidation although it could play an important role in the course of the oxidation process. These results could contribute to highlight some remaining questions regarding tamoxifen’s metabolic behavior and to the development of new analytical strategies, based on electrochemical approaches.